Efficacy of Transcranial Direct Current Stimulation Coupled with a Multidisciplinary Rehabilitation Program for the Treatment of Fibromyalgia - Riberto, Marcelo (Bentham Open, 2011)
Pain control in fibromyalgia patients is limited no matter the therapeutic regimens used. Recent data have shown that daily sessions of anodal transcranial direct current stimulation (tDCS) over the primary motor cortex (M1) in patients with fibromyalgia (FM) are associated with reduction of pain perception. OBJECTIVE: We aimed to test whether active tDCS, as compared with sham tDCS, combined with multidisciplinary rehabilitation is associated with significant clinical gains in fibromyalgia. DESIGN: This was a randomized, double-blinded controlled trial. SUBJECTS: 23 patients were randomized to receive weekly sessions of multidisciplinary rehabilitation approach combined with sham or anodal tDCS of M1. Patients were evaluated for pain with VAS and for quality of life with SF-36, fibromyalgia pain questionnaire and health assessment questionnaire by a blinded rater before and after the 4 month period of rehabilitation. RESULTS: Patients tolerated tDCS treatment well, without adverse effects. Patients who received active treatment had a significantly greater reduction of SF-36 pain domain scores (F((2,21))=6.57; p=0.006) and a tendency of higher improvement in Fibromyalgia Impact Questionnaire (FIQ) scores after (p=0.056) as compared with sham tDCS/standard treatment, but no differences were observed in the other domains. CONCLUSIONS: Although active tDCS was associated with superior results in one domain (SF-36 pain domain), the lack of significance in the other domains does not fully support this strategy (weekly tDCS) combined with a multidisciplinary approach.